Ritual roots of the Ancient and Accepted Scottish Rite in the Novohispanic and Mexican Masonic traditions from the 19th to the 21st centuries - Martínez Moreno, Carlos Francisco (2022)
The rituals of the Ancient and Accepted Scottish Rite have antecedents in an Order of the 18th century and in legends linked to Frederick King of Prussia. The Ancient Scottish masonic rituals were the basis of the regular Supreme Councils of the world, with a transcendent, cabalistic "secret" content, which may have been lost. Other irregular groups from Europe, the USA, and the Caribbean, rooted their traditions in New Spain and Mexico. Some ideas of their rituals affect their doctrine until the 21st century, using it for mostly political purposes, anticlericalism, and intolerance against other Masonic rites.